Influence of phyllody disease on VAM colonization in two cultivars of sesame - and S.R. REDDY, K.M. SHAILAJA, P. PAVAN KUMAR (Indian Phytopathology, 2002)
The influence of sesame phyllody, an important phytoplasmal disease of sesame, on VAM colonization was studied in the cultivars Rajeshwari and Gowri, uprooted from the same field locations. Both healthy and infected plants of the 2 sesame varietiesexhibited mycorrhizal colonization. The percentage VAM colonization was more in Rajeshwari than Gowri, and in both cultivars the colonization was greater in infected plants than healthy plants. Vesicles and mycelium were associated with all types of plants but arbuscules were only present in infected plants of both cultivars. Glomus fasciculatum and Sclerocystis rubiformis were observed in all 4 types of plants. Glomus mosseae was associated with healthy and diseased plants of Rajeshwari only and Acaulospora morrowea was recorded in the rhizosphere soil of healthy plants of the Gowri cultivar.